Bioimpedance Spectroscopy in Healthy Children. Issue 1 (January 2016) - Brantlov, Steven; Andersen, Trine Borup; Jødal, Lars; Rittig, Søren; Lange, Aksel
Abstract : Prediction equations compromise the usefulness of bioimpedance spectroscopy (BIS) in children. This preliminary study explored the possibility of establishing reference curves in children, based on BIS-modeled data and/or resistance index (RI) values. In addition, the precision of repeated measurements was calculated. A total of 105 children (2-14 years old) were enrolled. A BIS device was used and a wrist-ankle electrode configuration was applied. Three repeated measurements were performed in each child. Strongest correlations were seen between RI values and weight for both sexes range, r = 0.94 to 0.97, P < .001. The precision (coefficient of variation in percent) of repeated measurements showed to be low (range, 0.4% ± 0.3% to 1.1% ± 3.1%) We established sex-specific reference curves of RI values, and the precision of repeated measurements showed to be excellent.